Suplementasi Nutrien Defisien untuk Meningkatkan Penggunaan Daun Rami (Boehmeria nivea, L. Gaud) dalam Ransum Domba - . Despal (Media Peternakan, 2007)
A research to improve ramie leaf utilization in local sheep ration by supplementation of deficient nutrients was conducted. Four rations as treatments were tested using 12 local sheep (16.5 ± 1.6 kg LW) in a block randomized design. The treatments were T1 = 3% BW of DM native grass; T2 = T1 + 0.75% BW (25% of DM native grass) of DM ramie leaf; T3 = T2 + supplements Cu, P and methionine; T4 = T1 + 1.5% BW (50% of DM native grass) of DM ramie leaf + supplements Cu, P and methionine. Ration consumptions and digestibility, plasma level of Ca and P and body weight changed were determined. Dry matter intake increased in line with level of ramie leaf offered and there were no significantly difference on digestibility between the rations. Native grass alone failed to give a positive body weight change of local sheep. Addition of 25% DM ramie to native grass (T2) increased intake of digested nutrient and reduced body weight loss. Addition of supplement (T3) at the same level of ramie leaf increased intake of digested nutrient and changed the curve slope to the positive direction after the third week of observation. Addition of 50% DM ramie leaf to native grass basal ration followed by supplementation (T4) improved intake of digested nutrient closed to recommended nutrient requirement and showed a positive body weight changed. Key words: Boehmeria nivea, nutrient deficiency, sheep